The bilateral approach to reducing international mobile roaming charges and the application of the GATS - Michael H. Ryan (International Telecommunications Society (ITS), 2012)
Although it is generally acknowledged that international mobile roaming charges are too high, a successful formula for achieving reduction has so far proven elusive. Direct regulatory intervention to lower prices may be required. The success of such an approach depends upon the ability of countries to implement mutual reductions in the inter-operator tariffs (IOTs) that mobile operators charge each other for originating and terminating roaming calls. In the absence of a multilateral response, some countries have entered into bilateral arrangements to reduce IOTs. Questions have been raised about the compatibility of such bilateral arrangements with countries' obligations under the General Agreement on Trade in Services (the GATS), which generally forbids member countries from maintaining preferential arrangements with other countries that affect international trade in services. I identify and discuss two issues that arise about the application of the GATS to these bilateral arrangements: (1) How do the provisions of the GATS requiring parties to treat each others' service suppliers 'no less favourably' than they treat service suppliers of other countries and to offer non-discriminatory terms for network access apply to such bilateral arrangements? (2) Given that the GATS applies only to official measures affecting international trade in services, how does the GATS apply to bilateral arrangements between mobile operators which are ostensibly private in character but which are concluded at the instigation of officials? As I note in the conclusion, these issues have yet to be resolved.
Keywords: 330; regulation; international trade; telecommunications; international roaming; WTO; GATS